Discovery of novel S1P2 antagonists. Part 2: Improving the profile of a series of 1, 3-bis(aryloxy)benzene derivatives. Issue 20 (15th October 2015) - Kusumi, Kensuke; Shinozaki, Koji; Yamaura, Yoshiyuki; Hashimoto, Ai; Kurata, Haruto; Naganawa, Atsushi; Ueda, Hideyuki; Otsuki, Kazuhiro; Matsushita, Takeshi; Sekiguchi, Tetsuya; Kakuuchi, Akito; Seko, Takuya
Graphical abstract